2015
DOI: 10.1002/2015jd023241
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia and methane dairy emission plumes in the San Joaquin Valley of California from individual feedlot to regional scales

Abstract: Agricultural ammonia (NH3) emissions are highly uncertain, with high spatiotemporal variability and a lack of widespread in situ measurements. Regional NH3 emission estimates using mass balance or emission ratio approaches are uncertain due to variable NH3 sources and sinks as well as unknown plume correlations with other dairy source tracers. We characterize the spatial distributions of NH3 and methane (CH4) dairy plumes using in situ surface and airborne measurements in the Tulare dairy feedlot region of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 82 publications
3
42
0
Order By: Relevance
“…But, waste cleaning time/practices in the facility were unknown, owing to no access to the facility. Previous mobile and aircraft measurements have also observed enhancements of NH 3 and CH 4 concentrations downwind of animal pens in cattle feedlots (Miller et al, 2015;Hacker et al, 2016). The time variations of two VOCs, acetic acid and acetone, followed reasonably well with both NH 3 and CO 2 , suggesting that animals and their waste contributed to the enhancements of the two VOCs.…”
Section: Methodsmentioning
confidence: 50%
“…But, waste cleaning time/practices in the facility were unknown, owing to no access to the facility. Previous mobile and aircraft measurements have also observed enhancements of NH 3 and CH 4 concentrations downwind of animal pens in cattle feedlots (Miller et al, 2015;Hacker et al, 2016). The time variations of two VOCs, acetic acid and acetone, followed reasonably well with both NH 3 and CO 2 , suggesting that animals and their waste contributed to the enhancements of the two VOCs.…”
Section: Methodsmentioning
confidence: 50%
“…PFA tubing then brings sample flow from the inertial inlet box to the QC-TILDAS, which is co-located in the same equipment rack inside the aircraft cabin. As shown in previous studies, PFA tubing and fittings are used wherever possible along the sample pathway, and tubing lengths are kept to a minimum and heated wherever possible (Neuman et al, 1999;Schmohl et al, 2001;Mukhtar et al, 2003;Leifer et al, 2017). Components housed within the aircraft inlet strut are heated to 40 • C. The tubing between the inlet strut and the inertial inlet and between the inertial inlet and the QC-TILDAS are not actively heated; however, they are wrapped in flame-resistant polymer felt (DuPont Nomex) for thermal isolation.…”
Section: Aircraft Inletmentioning
confidence: 99%
“…Its accurate spectroscopic parameters are needed for a variety of gas‐sensing applications including those for environmental monitoring, industrial process control, and human breath analysis in medical science (e.g., Manne et al, ; Owen & Farooq, ; Schilt et al, ). While each of these applications involved significant concentrations of water vapor in the system, the impact of water vapor on ammonia absorption features is not negligible for high‐sensitivity detections of ammonia to ppb or ppm levels (D. J. Miller et al, ; Sun et al, , ). In fact, recent experimental results from Schilt () had demonstrated that water vapor was a significant cross‐sensitivity source especially in a high‐temperature environment.…”
Section: Generated Data Setsmentioning
confidence: 99%
“…While each of these applications involved significant concentrations of water vapor in the system, the impact of water vapor on ammonia absorption features is not negligible for high-sensitivity detections of ammonia to ppb or ppm levels (D. J. Miller et al, 2015;Sun et al, 2015Sun et al, , 2017. In fact, recent experimental results from Schilt (2010) had demonstrated that water vapor was a significant cross-sensitivity source especially in a high-temperature environment.…”
Section: Nhmentioning
confidence: 99%